Trauma Centre admission criteria for elderly patients - Sulej-Niemiec, Małgorzata; Kopta, Andrzej; Żurowska-Wolak, Magdalena; Bogacki, Paweł; Szura, Mirosław (Polski przeglad chirurgiczny, 2024)
Introduction: Injuries are among the three most common causes of sudden death in Poland, and patients particularly at risk of fatal outcomes of trauma are elderly. Geriatric age is associated with pathological changes that determine a worse response to trauma. In order to improve treatment outcomes of elderly trauma patients, it is essential for them to have access to specialized healthcare units i.e. Trauma Centers (TC). In Poland, admission criteria for TC are determined in the Regulation of the Ministry of Health published in 2010. Those criteria do not include age. According to recent research, such admission criteria lead to undertriage i.e., underestimation of injuries of elderly trauma patients and referred to a healthcare unit of lower reference level.Aim: Analyze the current national admission criteria of elderly trauma patients admitted to TCs.Materials and methods: TC admission criteria were subject to analysis in referral to available scientific publications in the field of medical segregation of elderly trauma patients, available in PubMed, Medline-EBSCO.Results: TC admission criteria in current form are fulfilled only by elderly patients with minimal survival chance. As a result, majority of elderly trauma patients are referred to healthcare units of lower reference level. Those patients are deprived of professional trauma care in TC. Such discrepancies in medical segregation often stem from lack of anatomical changes or shifts in physiological parameters typically observed in trauma patients.Conclusions: It is essential to develop national research to find the optimal system of triage for elderly trauma patient and an adequate tool for appropriate admitted them to TC.